The Position of the Head of Heir Mamak and His Authority in the Scope of Traditional Heirloom Land in the Minangkabau Indigenous Community in West Sumatra - Nalardi, Nalardi (Jurnal Konstatering, 2024)
This research aims to analyze: 1) The distribution of heritage within the Minangkabau Indigenous Community in West Sumatra. 2) The position of the chief heir mamak and his authority within the scope of traditional high inheritance land in the Minangkabau traditional community in West Sumatra. The approach method used in this research is an empirical (sociological) approach. The type of this research is analytical descriptive research. The types and sources of data in this research are primary and secondary data obtained through interviews and literature studies. The analysis in this research is descriptive analysis. Results The research concluded: 1) The division of inheritance in the Minangkabau Indigenous Community in West Sumatra is divided into inheritance and livelihood assets. Concerning livelihood inheritance assets, it must first be reviewed whether the assets have been partially or completely gifted to their children or nephews. When they have been gifted, of course the part that was gifted is the right of the person concerned. If leftovers are found then they are distributed to the children, the bako (fraternity of the father's family) asks or demands a share of the inheritance which will be resolved in litigation. 2.) The position of the chief heir mamak and his authority within the scope of customary high inheritance land in the Minangkabau traditional community in West Sumatra, namely as a clan leader who is fully responsible for the safety and welfare of members of the clan with the utilization and management of said high inheritance property, as a representative of the clan affairs of going out and acting inward for and on behalf of the clan, as well as the understanding that everything is in the hands of the head of the heir, as a mediator and the person who will resolve a dispute that occurs between members of the clan, whether personal problems in daily interactions or problems of inheritance, as a representative of the clan in court, for example as a defendant or as a plaintiff, as a representative of the clan in carrying out transactions on inherited land of the clan after obtaining approval from all members of the clan, for example selling and mortgaging inherited land, as a representative of the clan in matters of registration of inherited land, because the land is inherited must be registered in the name of the head of the inheritance, as the representative of the clan in the tribal density, as the person responsible for going out in traditional ceremonies within the clan, as the person responsible for paying land and building tax (PBB) on the clan's inheritance land.